Dutch Studies - Brachin, P. author. aut Link
XII, 216 p.
Keywords: The language of some eighteen million people living at the junction of the two great cultures of western Europe, Romance and Germanic, is now taught by some 262 teachers at I43 universities outside the Netherlands, ineluding Finland, Hungary, Poland, Russia, Czecho slovakia, Portugal, Japan, Malaysia and South Korea. These teachers obviously need to keep in regular and elose touch with the two countries whose culturallife forms the subject of their courses. Yet the first international congress of Dutch teachers abroad did not take place until the early sixties, since when the Colloquium Neerlandicum has become a triennial event, meeting alternately in the Netherlands and Belgium, in The Hague (I96I and I967), Brussels (I964) Ghent (I970) with the fifth Colloquium planned for Leiden in I973. Financial support from the Dutch and Belgian governments enables the majority of European colleagues, and a number of those from other continents, to attend a conference lasting for four or five days and ineluding discussions of the problems involved in teaching Dutch abroad and papers on various aspects of current Dutch studies of interest to those who are working in a certain degree of isolation abroad. At the first Colloquium a Working Committee of Professors and Lecturers in Dutch studies at Universities abroad was set up.